(untitled) (Journal Of Educational and Psychological Researches, 2022)
The aim of this research is to diagnose the attention deficit hyperactivity disorder among primary school pupils in Baquba city of Diyala province. The sample of the study consisted of (25) male and female pupils. The American Guide of Attention Deficit Hyperactivity Scale (DSM-IV, 1994) was used in this study in addition to Conner’s (1996) scale to measure the attention deficit hyperactivity disorder for teachers and parents. The result revealed that (19) male and female pupils diagnosed with attention deficit hyperactivity to various degrees.